Relationships between basin area and sediment yield upstream Shiroro reservoir, north-central Nigeria - Daramola Japheth; Lam, Kuok Choy; Mohd Ekhwan Toriman; Mokhtar Jaafar (Penerbit Universiti Kebangsaan Malaysia, 2020)
Sediment yield and basin area relationship in a watershed is a very crucial factor in Best Management Practices (BMPs) and reservoir sustainability. Therefore, the study was conducted to examines the suspended sediment concentration (SSC) of the four sub-watersheds of Kaduna watershed north-central Nigeria to aid the dam sustainability and BMP within the watershed. Water samples were collected bimonthly for 8 months (March-October 2018) and subjected to laboratory analysis for SSC and turbidity measurements. With the aid of ArcSwat2012, the watershed was delineated into four sub-watersheds, soil and land-use were classified for a proper understanding of the watershed. The findings demonstrated an inverse relationship between the size of the sub-watersheds and SSC. The smallest Dinya sub-watershed (1%) contributes approximately 25% (3781.5mg/l) of the SSC while the largest Kaduna (80%) contributes approximately 26% (3889mg/l), Sarkinpawa (11%) and Gutalu (8%) contributes approximately 26% (3844mg/l) and 23% (3444mg/l) of SSC respectively. The highest average turbidity was recorded in Sarkinpawa sub-watershed, followed by Dinya, Gutalu, and Kaduna. The SSC and turbidity results followed the rainfall pattern while the regression results for the four subwatersheds shows a good level of linearity between SSC, rainfall and turbidity, Therefore, it is recommended that sediment management practice is to be carried out along sub-watersheds Dinya and Sarkinpawa and Gutalu to reduce the high rate of sediment influx into the reservoir from these smaller sub-watersheds. Also, detail study of the smaller sub-watersheds is highly recommended for a better understanding of the factors responsible for high sediment generation in these sub-watersheds.